THE CAUSAL RELATIONSHIP BETWEEN ECONOMIC SERVICES EXPENDITURE AND ECONOMIC GROWTH IN NIGERIA - Bappayaya, Bashir; Abraham Alexander, Anfofum; Saheed, Zakaree; Imoudu Egwaihinde, Christian; Solomon Oyefabi, Ilemobola; Babayo, Hajara (African Journal of Social and Behavioural Sciences, 2026)
Numerous studies have examined the causal relationship between economic services expenditure and economic growth, but it is difficult to say for sure if the direction of causality is beneficial for economic growth. This study is crucial because prior empirical findings' conclusions have not been universally accepted. The aim of this study, therefore, is to investigate the causal relationship between economic services expenditure and the growth of the Nigerian economy for the period of 1981 to 2022. The study applied VECM, ADF and the Granger causality test using secondary data sourced from the CBN statistical bulletin. The study found that the components of economic services expenditure and the rate of economic growth in Nigeria have long-term correlations, and there is a causal relationship between economic services expenditure and the growth of the Nigerian economy in line with Keynesian theory. The study therefore recommends that the government increase its spending on roads and construction, transport and communication, and the federal government's extra-budgetary allocation to stimulate economic growth. Also, a high degree of transparency and accountability on government spending becomes a prerequisite in all sectors of the economy in order to prevent mismanagement or misappropriation of funds.